P128 Accuracy of the combination of transabdominal and transperineal ultrasound for the evaluation of Ulcerative Colitis activity. (21st January 2022) - Terracciano, F; Bossa, F; Marra, A; Valvano, M R; Carparelli, S; Ippolito, M A; Perri, F
Abstract: Background: Transabdominal Bowel Ultrasound (TBUS) is useful technique to assess disease activity and extent in patients with ulcerative colitis (UC); however, the evaluation of the rectum by TBUS is difficult. Recently, transperineal ultrasound (TPUS) has been proposed as a useful diagnostic tool in the evaluation of rectal disease. The aim of the study is to to assess the concordance between the combination of TPUS/TBUS and endoscopy in adult patients with UC. Methods: Fifteen consecutive adult patients with UC were prospectively enrolled from June to November 2021. Disease activity was determined using Partial Mayo Score (PMS) and Mayo Endoscopic Subscore (MES). TBUS and TPUS were performed within a week from endoscopy. MES ≤ 1, bowel wall thickness ≤ 3mm in the colon and ≤ 4mm in the rectum were defined as remission. A concordance analysis comparing endoscopy and US was performed by kappa statistics Results: Ten patients were male (66%) and 8 female (34%), with a median age of 39± 13, 9. Two patients had a pancolitis, 6 a distal colitis, and 3 a proctitis. 4 patients were in remission. The agreement between endoscopy and rectal evaluation with TBUS was fair (k =0.40), while the agreement with TPUS was excellent (k =0.86). The evaluation of the colon with TBUS showed good concordance in the right colon (k= 0.63), left colon (k=0.65), and sigmoid colon (k=0.72), and excellent agreement in the transverse colon (k= 1). Conclusion: These preliminary data showed that the combination of TBUS and TPUS allows to easily and accurately study all the segments of the large intestine in patients with UC, overcoming the limitation related to the reduced accessibility to the rectum with only trans abdominal approach.